Perceived usefulness of conceptual maps by higher education students - Chambi Mescco, Edith (2020)
The purpose of the present work was to identify the usefulness of the conceptual maps that the first cycle students of general studies of a Peruvian public university perceive. Students produced various concept maps to represent their conceptual understanding through the Cmap Tools program. The methodology of this study corresponds to the quantitative approach, so the Concept Mapping Questionnaire (CMQ), in its Spanish version, was applied to 70 students enrolled in the 2019-I academic period. The results show that most of the students consider that concept maps are useful to some extent, mainly because it has helped them to clarify the interrelationships between the contents of the subject, to think independently and to better understand their learnings.